Aplikasi Kurir Mobil Pick Up Berbasis Mutli Platform - Novaely Rachman; Pahrul Irfan (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
Problem faced by goods delivery service providers today is that there are found consumers they have difficulty in finding couriers to transport large goods, thus causing consumers to have to go to the owner of a pickup car or delivery service provider, it can take a lot of time and cost. To solve the problem, there is currently no system that facilitates consumers in ordering couriers optimally. Therefore, it requires a delivery system that can order couriers only through a smartphone owned. The result that was wanted to be achieved in this study was the creation of a multiplatform based courier ordering system with a REST web service architecture that can be accessed through computer and Android platforms. With the construction of this system testing of the web service, the test results of the web service function stated that, all functions tested show valid results, this means that the entire web service function on the application, already fulfilled the design, in addition to testing against the web service, conducted also the black box trial, based on the black box test results, it is concluded that the application created, already according to the design, is proven by all the parts tested showing valid status